Diagnosis and Management of Metastatic Breast Cancer During Pregnancy by a Multidisciplinary Team: A Case Report - Mohamadianamiri, Mahdis; Aklamli, Majid; Shojaei, Seyedeh Fahimeh (Archives of Breast Cancer, 2019)
Background: When breast cancer is diagnosed during pregnancy or within the first year after delivery, the condition is named as pregnancy-associated breast cancer (PABC). Breast cancer during pregnancy is a devastating situation for the patient, her family, and the medical team. Providing guidance for diagnosis and treatment of PABC, we report a case along with review of the literature. Case presentation: Here we present a 31-year-old pregnant woman with low back pain who was referred to the gynecology ward. She was at 25 weeks and 6 days pregnancy. After workup, it was discovered that she had a lytic lesion in her spine. Further workup revealed that she had metastatic breast cancer with the pathology of invasive ductal carcinoma. After consultation with a multidisciplinary team (a gynecologist, an oncologist, a radiotherapist, a hematologist-oncologist, and a neurosurgeon), we terminated the pregnancy and put her on radiotherapy for the spine metastasis and systemic therapy. Also, we reviewed 36 pregnant patients with primary or recurrent breast cancer who were managed with outpatient chemotherapy, surgery, or surgery plus radiation therapy. Care was provided by medical oncologists, breast surgeons, and perinatal obstetricians. Conclusion: Since there are no sufficient data in the literature to guide the development of standard protocols for management of PABC patients (specially in metastatic disease), pregnant women must be followed up by a multidisciplinary team, and each case should be managed considering the gestational age and the stage of cancer.